Woman and to-morrow - George, W. L., 1882-1926. (London : Herbert Jenkins, 1913)
George argues that women must move beyond the issue of suffrage and confront their confinement to the home; only thus will they effect significant social change.
Keywords: Women -- Social and moral questions; Women -- Social and moral questions